2011
DOI: 10.1002/app.34004
|View full text |Cite
|
Sign up to set email alerts
|

Diazotization‐iodination of aromatic amines in water mediated by crosslinked poly(4‐vinylpyridine) supported sodium nitrite

Abstract: An Efficient and simple method for the diazotization of a wide range of aryl amines has been developed by using a polymer-supported sodium nitrite. The diazotization of aryl amines occurred with crosslinked poly(4-vinylpyridine)-supported sodium nitrite, in the presence of concentrated H 2 SO 4 , at low temperature (0-5 C). The obtained diazonium salt, followed by treatment with KI in water at room temperature or at 60 C to produce a various of aryl iodides. The spent polymeric reagent can be regenerated and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 50 publications
2
13
0
Order By: Relevance
“…It is important to note that this polymeric reagent was stable and could be stored for a long time (months) without losing its activity; it could be readily used for the diazotization–cyanation of anilines. [P 4 ‐VP]I was recently prepared and used for the preparation of other functionalized polymers, including polymer‐supported thiocyanate, polymer‐supported carboxylate, polymer‐supported potassium ferrate, polymer‐supported azide ion,51 and polymer‐supported nitrite ion 46–50. Although [P 4 ‐VP]I is well known, [P 4 ‐VP]CN was used the first procedure for the direct diazotization–cyanation of aryl amines, and on the basis of our knowledge, there has been no report in the literature on the synthesis of aryl nitriles based on polymer‐supported cyanide ion.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is important to note that this polymeric reagent was stable and could be stored for a long time (months) without losing its activity; it could be readily used for the diazotization–cyanation of anilines. [P 4 ‐VP]I was recently prepared and used for the preparation of other functionalized polymers, including polymer‐supported thiocyanate, polymer‐supported carboxylate, polymer‐supported potassium ferrate, polymer‐supported azide ion,51 and polymer‐supported nitrite ion 46–50. Although [P 4 ‐VP]I is well known, [P 4 ‐VP]CN was used the first procedure for the direct diazotization–cyanation of aryl amines, and on the basis of our knowledge, there has been no report in the literature on the synthesis of aryl nitriles based on polymer‐supported cyanide ion.…”
Section: Resultsmentioning
confidence: 99%
“…In the conversion of aryl amines to the corresponding aryl nitriles, a 3/2 molar ratio of [P 4 ‐VP]CN to amine was needed, although in the conversion of aryl amines to the corresponding aryl iodide, a 3/1 molar ratio of [P 4 ‐VP]I to amine was needed (Table II). 50…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although polymer‐supported reagents especially anion exchange resins have been widely applied in organic synthesis,46–62 a literature search shows that there are a few reports in organic transformation based on polymer supported azide reagent. Brenelli et al reported that Amberlite IRA 900 supported azide resin is a highly effective reagent for the conversion of α‐haloketones into α‐azidoketones 59.…”
Section: Introductionmentioning
confidence: 99%